Maturity, resilience & lifecycles in suburban residential areas. - Polívka, Jan (My University, 2016)
Most of the suburban residential areas in Germany have been built during the second half of the 20th century. Growing interest among practitioners and scientists is thus paid to the future development of maturing settlement areas characterized by old housing stock and aging inhabitants. This dissertation analyzes processes of change and adaption of suburban residential areas under the conditions of the maturation process. The analysis aims on contributing to the systemic notion of processes changing maturing systems within their natural lifecycle and its interdependence with deliberate adaption under particular stakeholders constellations. On the theoretically conceptual level it seeks to explore the key attributes of the development path for evolutionary lifecycles within the context of resilience, discussing the phenomena of stable maturity and continuous adjustment and on the concept of settlement space. By deconstructing the lifecycle concept, the book analyzes the canonical view on mature suburbia based in the traditional growth-maturity-decline pattern and introduces a pluralistic concept of path dependent evolution based on a multileveled interdependence between particular levels of space, stakeholders panarchy and adaptive action. On behalf of outcomes based in theory and the results from two empirical studies conducted in German mature suburban residential areas, a concept of multi-leveled systemic space as both interpretative and analytic tool for understanding development paths of mature suburban systems is introduced. The results of its application on the case studies show that, especially in terms of homogeneity and diversity, lifecycles of suburban residential areas underlie different conditions for change and adaption during the early and the maturity phases, and defines interpretative frames for conceptualizing both theiretical and research approaches.
Keywords: Stadtentwicklungsplanung; Siedlungsentwicklung; Wohngebiet; Wohnanlage; Suburbanisierung; Siedlungstyp; Wohngebäude; Einfamilienhaus; Vorort; Alterung; Bewohner; Fallstudie; Gebäudealter; Lebenszyklus; Wohnungsanpassung; Demographischer Wandel